2014
DOI: 10.1038/nature13473
|View full text |Cite|
|
Sign up to set email alerts
|

Activation and repression by oncogenic MYC shape tumour-specific gene expression profiles

Abstract: In mammalian cells, the MYC oncoprotein binds to thousands of promoters. During mitogenic stimulation of primary lymphocytes, MYC promotes an increase in the expression of virtually all genes. In contrast, MYC-driven tumour cells differ from normal cells in the expression of specific sets of up- and downregulated genes that have considerable prognostic value. To understand this discrepancy, we studied the consequences of inducible expression and depletion of MYC in human cells and murine tumour models. Changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

46
537
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 425 publications
(598 citation statements)
references
References 38 publications
(48 reference statements)
46
537
4
Order By: Relevance
“…35 Furthermore, it has been suggested that due to an invasion of low-affinity sites in promoters and enhancers, high levels of MYC can regulate additional gene expression programs, including those involved in apoptosis. 6,8 Last, complex formation with other transcriptional regulators such as MIZ1 can modulate transcriptional responses upon MYC overexpression. 6,7 It is likely that these quantitative changes in gene expression patterns represent essential molecular cues that allow differentiation between physiological and oncogenic levels of MYC and, ultimately, crossing of the apoptotic "threshold."…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…35 Furthermore, it has been suggested that due to an invasion of low-affinity sites in promoters and enhancers, high levels of MYC can regulate additional gene expression programs, including those involved in apoptosis. 6,8 Last, complex formation with other transcriptional regulators such as MIZ1 can modulate transcriptional responses upon MYC overexpression. 6,7 It is likely that these quantitative changes in gene expression patterns represent essential molecular cues that allow differentiation between physiological and oncogenic levels of MYC and, ultimately, crossing of the apoptotic "threshold."…”
Section: Discussionmentioning
confidence: 99%
“…6,8 Last, complex formation with other transcriptional regulators such as MIZ1 can modulate transcriptional responses upon MYC overexpression. 6,7 It is likely that these quantitative changes in gene expression patterns represent essential molecular cues that allow differentiation between physiological and oncogenic levels of MYC and, ultimately, crossing of the apoptotic "threshold." 36 We demonstrated previously that association with MIZ1 and subsequent repression of target genes of the SRF transcription factor are required to induce apoptosis in response to oncogenic MYC levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MYC alone is sufficient to initiate tumors and to drive tumor progression in the pancreas in vivo (5,(7)(8)(9)(10). Furthermore, compelling evidence exists that MYC is an essential downstream effector of oncogenic KRAS in the pancreas (11)(12)(13)(14). MYC expression is controlled at several layers in PDAC (15).…”
mentioning
confidence: 99%